Comparison of urinary excretion of Deoxypiridinoline and value of serum Osteocalcin within the Knee Osteoarthritis grading (Medical Journal of Indonesia, 2004)
The identification of molecular markers, which reflects differences in disease progression rates in Osteoarthritis (OA), would greatly facilitate clinical studies. Urinary Deoxypyridinoline (UDPD) and serum osteocalcin (OC) had been widely used for marker of bone metabolism, but the use for molecular marker in OA was lack of data. Recent studies show that there were conflicted results between urinary excretion of DPD and serum OC value within knee OA grading. The aim of this study is to compare of urinary excretion of DPD and the level of serum OC as destructive parameter of cartilage within the knee OA grading. This cross sectional study comprise of 69 patients with OA of knee joints. Kellgren and Lawrence scale was use for grading of OA. Group of patients with knee OA grade 2 call as group of early OA and group of patients with knee OA grade 3 and 4 calls as group of late OA. DPD in urine was measured using Immuno-chemilunescence, serum osteocalcin was measured using Elisa method. The mean value of urinary concentrations of DPD in OA patients was higher than normal value (9.79 ± 7.28 nM DPD/mM Creatinin), and the mean value of serum OC within normal value (8.49 ± 4.68 ng/mL). There were no significant differences of age, body mass index (BMI), duration of illness, urinary excretion of UDPD and serum OC level between early and late OA. In conclusion, there is no significant difference of urinary excretion of DPD and serum OC level within knee OA grading. The use of urinary DPD and serum OC as molecular markers of progression of OA needed to be explored by other longitudinal study. (Med J Indones 2004; 13: 96-101) Keywords: Knee osteoarthritis, deoxypiridinoline, osteocalcin